Border villages and the suffering of Kolberi: focus on Kolbers mothers’ narratives of their children’s Kolberi experience - Daneshmehr, Hossein; Khaleghpanah, Kamal; Sobhani, Parviz; Rostami, Susan (Frontiers in Sociology, 2024)
IntroductionThe present research investigates the activity of Kolberi in the border villages of western and northwestern Iran, specifically in the Kurdish area of Nosud in Kermanshah province. Kolberi, a form of labor in these regions, subjects individuals to severe risks, including painful death or lifelong physical injuries, bringing considerable suffering and hardships to the Kolbers and their families. This study explores the narratives of Kolbers’ mothers regarding their children’s Kolberi experiences through Pierre Bourdieu’s theoretical framework of social suffering.MethodsThis qualitative study employs interpretive phenomenology to examine the lived experiences of mothers in the Nosud border area. Twenty-two Kolbers’ mothers were selected using purposive sampling. Data collection was conducted through semi-structured interviews and participant observation, continuing until theoretical saturation was achieved.ResultsContent analysis of the interviews revealed eight basic themes: (1) occurrence and aggravation of physical and mental complications, (2) reproduction of poverty and misery, (3) marginalization of the field of education in border areas, (4) emergence of structural determinism alongside environmental determinism, (5) weakening of the social status of Kolbers, (6) Kolber and bare life, (7) structural dehumanization of Kolber’s position, and (8) unique experiences of mothers regarding Kolberi.DiscussionThe findings highlight the unique and often neglected experiences of mothers related to Kolberi, emphasizing the economic struggles in Iran’s border areas. These experiences unveil hidden aspects of Kolberi, suggesting potential avenues for further research and contributing to the revitalization of activism among Kolbers’ mothers in border regions. The study underscores the importance of addressing the socio-economic conditions that perpetuate Kolberi and its associated sufferings.